1994
DOI: 10.1073/pnas.91.20.9292
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mechanics of kinetic proofreading in protein folding in vivo.

Abstract: The statistical energy lAndpe picture of protein folding has led to the understanding that the energy landscape must have guiding forces leading to a protein folding funnel in order to avoid the Levinthal paradox in vitro. Since folding in vivo often requires the action of chaperone molecules and ATP hydrolysis, we must ask whether folding in a system maintained away from equilibrium can avoid the Levinthal paradox in other ways. We describe a model of the action of chaperone molecules in protein folding in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 19 publications
1
47
2
Order By: Relevance
“…This seems a further development of the "kinetic proofreading" model of Gulukota and Wolynes (1994). Zahn and his colleagues further suggested that chaperonins have an ongoing annealing function (i.e., local bindinghnbinding) within the polypeptide-chaperonin complex, perhaps distinct from active unfolding (Zahn et al, 1996b).…”
Section: Conformational Changes In the Substrate Proteinmentioning
confidence: 98%
“…This seems a further development of the "kinetic proofreading" model of Gulukota and Wolynes (1994). Zahn and his colleagues further suggested that chaperonins have an ongoing annealing function (i.e., local bindinghnbinding) within the polypeptide-chaperonin complex, perhaps distinct from active unfolding (Zahn et al, 1996b).…”
Section: Conformational Changes In the Substrate Proteinmentioning
confidence: 98%
“…The cycle of ATP hydrolysis, release, partitioning, and rebinding (Fig. 2B It is useful to contrast the IAM to the kinetic proofreading model for chaperonin action (7). In the latter, the chaperonins are assumed to provide a bias in the folding to the native state that is argued to be responsible for the rate enhancement.…”
Section: Rugged Energy Landscapes and The Kinetic Partitioning Mechanismmentioning
confidence: 99%
“…We show here that these two seemingly disparate approaches to protein folding can be unified by the theory of iterative annealing to account for chaperonin-facilitated protein folding. Theoretical studies have also begun to consider the role of chaperonins in protein folding (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Eq. 1 has the form of the Ising spin-glass Hamiltonian, and a similar expression was used in the model of folding of proteins (17). Although Eq.…”
Section: Modelmentioning
confidence: 99%